2013
DOI: 10.1007/s11064-013-1114-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Assymetrical Noradrenergic Transmission in the Olfactory Bulb of Deoxycorticosterone Acetate-Salt Hypertensive Rats

Abstract: The ablation of olfactory bulb induces critical changes in dopamine, and monoamine oxidase activity in the brain stem. Growing evidence supports the participation of this telencephalic region in the regulation blood pressure and cardiovascular activity but little is known about its contribution to hypertension. We have previously reported that in the olfactory bulb of normotensive rats endothelins enhance noradrenergic activity by increasing tyrosine hydroxylase activity and norepinephrine release. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
6
3
0
Order By: Relevance
“…TH has four potential phosphorylation Ser-sites, three of which are intimately implicated in the activity of the enzyme (Ser19, Ser31 and Ser 40). Consistent with previous studies, the expression of TH-PSer19, TH-PSer31 and TH-PSer40 were increased in the OB of DOCA-Salt rats [14]. Blockade of ET A by BQ610, decreased the expression of the phosphorylated forms of the enzyme to control levels in hypertensive animals but induced no changes in normotensive rats (Figures 4c and 4d).…”
Section: Acute Brain Et a Blockade Decreased The Activity And Phospho...supporting
confidence: 91%
See 2 more Smart Citations
“…TH has four potential phosphorylation Ser-sites, three of which are intimately implicated in the activity of the enzyme (Ser19, Ser31 and Ser 40). Consistent with previous studies, the expression of TH-PSer19, TH-PSer31 and TH-PSer40 were increased in the OB of DOCA-Salt rats [14]. Blockade of ET A by BQ610, decreased the expression of the phosphorylated forms of the enzyme to control levels in hypertensive animals but induced no changes in normotensive rats (Figures 4c and 4d).…”
Section: Acute Brain Et a Blockade Decreased The Activity And Phospho...supporting
confidence: 91%
“…TH activity was enhanced in the OB of hypertensive animals as previously reported [14]. Blockade of ET A induced no changes in TH activity in normotensive animals, but it reduced the enzyme activity to control values in DOCA-Salt hypertensive rats (Figure 4a).…”
Section: Acute Brain Et a Blockade Decreased The Activity And Phospho...supporting
confidence: 86%
See 1 more Smart Citation
“…In a later study, we reported that long-term exposure to ETs enhances TH mRNA and the expression of total TH and its phosphorylation forms in normotensive rats [ 14 ]. Furthermore, to our knowledge, we were the first to report that in the right OB of DOCA-salt hypertensive rats TH activity and expression as well as neuronal norepinephrine release were increased whereas the uptake of the amine was diminished [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the left OB, the catecholaminergic activity was unchanged. We previously reported an asymmetrical behavior in the OB of DOCA-salt rats and non-asymmetrical differences in normotensive animals [ 40 ]. The existence of brain asymmetry, including norepinephrine levels in the hypothalamus, has been reported in distinct animal species [ 45 ].…”
Section: Discussionmentioning
confidence: 99%